4 V room-temperature all-solid-state sodium battery enabled by a passivating cathode/hydroborate solid electrolyte interface. Issue 12 (2nd November 2020) - Asakura, Ryo; Reber, David; Duchêne, Léo; Payandeh, Seyedhosein; Remhof, Arndt; Hagemann, Hans; Battaglia, Corsin
Abstract : A self-passivating cathode/electrolyte interface achieves stable, room-temperature long-term cycling of 4 V-class Na3 (VOPO4 )2 F|Na4 (CB11 H12 )2 (B12 H12 )|Na all-solid-state sodium batteries with the highest reported discharge cell voltage and cathode-based specific energy. Abstract : Designing solid electrolytes for all-solid-state-batteries that can withstand the extreme electrochemical conditions in contact with an alkali metal anode and a high-voltage cathode is challenging, especially when the battery is cycled beyond 4 V. Here we demonstrate that a hydroborate solid electrolyte Na4 (CB11 H12 )2 (B12 H12 ), built from two types of cage-like anions with different oxidative stability, can effectively passivate the interface to a 4 V-class cathode and prevent impedance growth during cycling. We show that [B12 H12 ] 2− anions decompose below 4.2 V vs. Na + /Na to form a passivating interphase layer, while [CB11 H12 ] − anions remain intact, providing sufficient ionic conductivity across the layer. Our interface engineering strategy enables the first demonstration of a 4 V-class hydroborate-based all-solid-state battery combining a sodium metal anode and a cobalt-free Na3 (VOPO4 )2 F cathode without any artificial protective coating. When cycled to 4.15 V vs. Na + /Na, the cells feature a discharge capacity of 104 mA h g −1 at C/10 and 99 mA h g −1 at C/5, and an excellent capacity and energy retention of 78% and 76%, respectively, after 800 cycles at C/5 at <0.2 MPa at room temperature. Increasing the pressure to 3.2 MPa enables a discharge capacity of 117 mA h g −1 at C/10 with a mass loading of 8.0 mg cm −2, corresponding to an areal capacity close to 1.0 mA h cm −2 . The cell holds the highest average discharge cell voltage of 3.8 V and specific energy per cathode active material among all-solid-state sodium batteries reported so far, emphasizing the potential of hydroborates as electrolytes for a competitive all-solid-state battery technology.